Wpływ globalizacji na polskie małe i średnie przedsiębiorstwa - Gunia Maciej (My University, 2008)
Globalization is not a new phenomenon in the contemporary economy. However, globalization as a term has spread in the early 90s of XX century and it is still being developed by economists. Nowadays globalization is not considered only as economic phenomenon. Very often we can find its understanding as a set of processes leading to intensification of relationships in the areas of economy, politics and culture over borders. According to Streeten (2002), globalization is a progressive process in which almost every company or enterprise is taking part. The main aim of my dissertation is to analyze and assess the impact of globalization on the sector of the small and medium sized-enterprises (SMEs) with a focus on the Polish SME sector. In order to reach the main aim I formulated the following specific goals: 1. Analyzing globalization as an economic phenomenon and the company strategic direction. 2. Presenting the characteristics and economic importance of the Polish SME sector. 3. Characterizing the internationalization of the Polish SMEs. 4. Identifying and assessing the opportunities and threats from globalization for the Polish SME sector. The first chapter of my dissertation is devoted to globalization as economic phenomenon and to strategic directions of companies in this regard. That requires introducing things like reasons and factors which stimulate globalization of industries. An extensive part of the chapter is devoted to stages of globalization (exporting – internationalization – globalization). The second chapter will deal with SMEs’ characteristics and importance for the Polish economy. Further, in the third chapter the internationalization of the Polish SMEs will be discussed. This chapter will consist of sections including basic internationalization strategies of SMEs, internationalization of SMEs in the European Union and internationalization of the Polish SMEs. Moreover, the place of the Polish SMEs in the globalization of economic activities will be discussed. In the fourth chapter, the SWOT analysis of the Polish SMEs facing globalization process will be exercised. The chapter will analyses opportunities and threats from globalization to the Polish SMEs sector, confronted with strengths and weaknesses of this group of companies. I will address the following research questions: What are characteristics of globalization of economic activities?; What are the international strategies of SMEs?; What are strengths and weaknesses of the Polish SMEs sector?; What are the characteristics of the internationalization of the Polish SMEs?; What is the role of SMEs in the globalization process?; What are threats and opportunities from globalization to the Polish SME sector? The thesis is of theoretical and empirical nature. The theoretical part consists of theory of internationalization and globalization of economic activities and of the properties of SMEs. The empirical part includes the analysis of SMEs’ economic condition as well as identification of their scope of internationalization and internationalization strategies. Further, the empirical part involves characterizing the SMEs’ role in globalization of economic activities and assessing threats and opportunities that arise from globalization to SMEs. I based my research on extensive literature review (books, papers and reports, internet resources) and secondary data analysis with the use of descriptive statistics and forecast methods. Moreover, I utilized SWOT as analytical method to integrate the main research outcomes. Also it is important to mention the time span on which I have focused in my research. The Polish economy has experienced enormous changes since 1989, when the communist system officially ended in Poland and capitalism took its place. During the time of communist regime, there was no chance (or extremely limited chances) to open a private business. Early 1990s brought the era of private enterprise. Since that time, lots of small and medium sized enterprises have been established. Gradually growing up and strengthening their position on the market. The late 1990s brought internationalization and bigger expansion of the Polish SMEs into foreign markets, which was even accelerated with Poland’s accession into the EU. My study concentrates on this period of expansion in the Polish economy, which started when Poland became an EU member, i.e. from 2004 to present.
The impact of globalization on the polish small and medium - sized enterprises
Keywords: globalization; global competitive strategies; Small and Medium sized Enterprises (SMEs); national economy; internationalization of SMEs; European Union